Marcadores tumorales en la detección y manejo del cáncer de la próstata - Vargas Delaunoy, Roberto (Revista Hospital Clínico Universidad de Chile, 1996)
TUMORAL MARKERS AS SCREENING TEST AND IN THE MANAGEMENT OF PROSTATE CANCER. The sensibility and specificity of prostatic serum antigen levels as screening test and in the management of prostatic cancer, is analized by the author.